PERBEDAAN PENGETAHUAN REMAJA PUTRI SEBELUM DAN SESUDAH DIBERIKAN EDUKASI VULVA HYGIENE SAAT MENSTRUASI MENGGUNAKAN MEDIA FLIPBOOK - Rahayu, Ni Made Yunita; Darmapatni, Made Widhi Gunapria; Mahayati, Ni Made Dwi (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025DO - 10.24843/ACH.2025.v12.i01.p31, 2025)
ABSTRACT Vulva hygiene during menstruation is a component that plays an important role in avoiding interference with the function of the reproductive organs. The purpose of this study was to determine the difference in knowledge of young women before and after being given education about vulva hygiene during menstruation using flipbook media. The method used in this study was pre-experimental with a pretest-posttest one group design. The data used in this study is primary data using a questionnaire and analysis with the wilcoxon test. This research was conducted at SMP Wisata Sanur in May 2023. The sample in this study was class VIII students. The number ofrespondents in this study totaled 51 people. The sampling technique used proportional random sampling. The results ofthe research before being given education the median value is 80, the minimum value is 50 and the maximum value is 95 and after being given education the median value is 85, the minimum value is 60 and the maximum value is 100.The Wilcoxon test results show that the value of p=0.000 is smaller than 0.05 so it can be concluded that there is a difference in the knowledge ofyoung women before and after being given education about vulva hygiene during menstruation using flipbook media. The results of this study will provide additional information for health workers to help improve promotional and preventive efforts by providing vulva gyfiene education to young women. Keywords:  Flipbook, Menstruation, Vulva hygiene